2022
DOI: 10.3390/polym14020255
|View full text |Cite
|
Sign up to set email alerts
|

Polysaccharides from Basidiocarps of the Polypore Fungus Ganoderma resinaceum: Isolation and Structure

Abstract: In this study, we focused on the isolation and structural characterization of polysaccharides from a basidiocarp of polypore fungus Ganoderma resinaceum. Polysaccharide fractions were obtained by successive extractions with cold water at room temperature (20 °C), hot water under reflux (100 °C), and a solution of 1 mol L−1 sodium hydroxide. The purity of all fractions was controlled mainly by Fourier transform infrared (FTIR) spectroscopy, and their composition and structure were characterized by organic eleme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 92 publications
(137 reference statements)
0
9
0
Order By: Relevance
“…4 The FTIR spectra of ASF-1, ASF-3, and ASF-7 showed peaks at 1077.1, 1051.7, and 1037.2 cm -1 , respectively which indicated the presence of a pyranose ring. 4,19,29 Additionally, a weak band of ASF-3 at 926.8 cm -1 associated with the β configurations of glycosidic linkages confirmed that ASF-3's monosaccharide was mainly glucose. Antioxidant assays DPPH (2,2-diphenyl-1-picrylhydrazyl) is a free radical capable of absorbing molecular hydrogen and antioxidants.…”
Section: Ft-ir Spectra Analysismentioning
confidence: 80%
See 2 more Smart Citations
“…4 The FTIR spectra of ASF-1, ASF-3, and ASF-7 showed peaks at 1077.1, 1051.7, and 1037.2 cm -1 , respectively which indicated the presence of a pyranose ring. 4,19,29 Additionally, a weak band of ASF-3 at 926.8 cm -1 associated with the β configurations of glycosidic linkages confirmed that ASF-3's monosaccharide was mainly glucose. Antioxidant assays DPPH (2,2-diphenyl-1-picrylhydrazyl) is a free radical capable of absorbing molecular hydrogen and antioxidants.…”
Section: Ft-ir Spectra Analysismentioning
confidence: 80%
“…Subsequently, 96% ethanol in a ratio of 1:3 (v/v) was added to precipitate the polysaccharide. 19 The resulting residue was neutralized, washed, and dried using the same process.…”
Section: Removal Of Proteins and Pigmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…16 It was reported that two polysaccharides obtained from Ganoderma resinaceum by water extraction proved to be a branched O-2-β- d -mannosyl-(1→ 6)-α- d -galactan and a highly branched (1→ 3)(1→4)(1→6)-β- d -glucan, respectively. 17 It is well-known that the structure of polysaccharides is the basis of their biological activities, and they are closely related. Therefore, it is of great importance to further study the structure of Ganoderma applanatum polysaccharides and to investigate the relationship between their structure and activity.…”
Section: Introductionmentioning
confidence: 99%
“…The presence and distribution of target bioactive components in the fruiting bodies (basidiocarps) and other parts of this fungus may depend on the genetic background, cultivation conditions, and developmental stage. There are many studies of cell wall macromolecules and secondary metabolites in Ganoderma basidiocarps based on various analytical methods, including photometric assays [10], different techniques of mass spectrometry (MS) [11][12][13][14], one-and two-dimensional (1D, 2D) nuclear magnetic resonance (NMR) spectroscopy [15][16][17][18][19], gas chromatography with MS detection (GC-MS) [20], high-performance liquid chromatography (HPLC) [10,21], and HPLC with MS [21][22][23][24] or NMR [25] detection. These methods exhibit high accuracy, selectivity, and sensitivity to the structure of the analytes.…”
Section: Introductionmentioning
confidence: 99%